2023
DOI: 10.1021/acsorginorgau.3c00025
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Lone Pairs Control Topology in Heterotrimetallic Complexes: An Experimental and Theoretical Study

Paulina Guerrero-Almaraz,
Manuel Quiroz,
David R. Rodriguez
et al.

Abstract: Heterotrimetallic complexes with (N 2 S 2 )M metallodithiolates, M = Ni 2+ , [Fe(NO)] 2+ , and [Co(NO)] 2+ , as bidentate chelating ligands to a central trans-Cr(NO)(MeCN) unit were characterized as the first members of a new class, NiCrNi, FeCrFe, CoCrCo. The complexes exhibit a cisoid structural topology, ascribed to the stereoactivity of the available lone pair(s) on the sulfur donors, resulting in a dispersed, electropositive pocket from the N/N and N/S hydrocarbon linkers wherein the Cr-NO site is housed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In search of different arrangement centers, we noted that synthetic efforts from the Richards and Louttit groups had produced a series of diphosphine ligands bound to {Mo­(NO)} 6 and {Cr­(NO)} 5 in a trans-configuration (Figure A). , Similar approaches with the Ni­(N 2 S 2 ) and (NO)­Fe­(N 2 S 2 ) complexes as ligands found that the thermodynamically stable trimetallic products linked with {Cr­(NO)} 5 were in the cissoid arrangement; the­[(NO)­Fe­(N 2 S 2 )] 2 Cr­(NO)­(CH 3 CN)] 2+ or [ FeCrFe ] 2+ product is shown in Figure B. The unique stereochemical behavior found in the “uncommon” isomer emerges from the additional lone pair(s) interactions on the sulfur donor atoms …”
Section: Sulfur Lone Pairs Control Topology (Case D)mentioning
confidence: 98%
See 3 more Smart Citations
“…In search of different arrangement centers, we noted that synthetic efforts from the Richards and Louttit groups had produced a series of diphosphine ligands bound to {Mo­(NO)} 6 and {Cr­(NO)} 5 in a trans-configuration (Figure A). , Similar approaches with the Ni­(N 2 S 2 ) and (NO)­Fe­(N 2 S 2 ) complexes as ligands found that the thermodynamically stable trimetallic products linked with {Cr­(NO)} 5 were in the cissoid arrangement; the­[(NO)­Fe­(N 2 S 2 )] 2 Cr­(NO)­(CH 3 CN)] 2+ or [ FeCrFe ] 2+ product is shown in Figure B. The unique stereochemical behavior found in the “uncommon” isomer emerges from the additional lone pair(s) interactions on the sulfur donor atoms …”
Section: Sulfur Lone Pairs Control Topology (Case D)mentioning
confidence: 98%
“…Inorg. Au 2023 , 3 , 393 . A central trans -Cr­(NO)­(MeCN) radical unit positions two (NO)­Fe­(N 2 S 2 ), S = 1/2 metalloligands in a cissoid structure 6 Å apart.…”
Section: Key Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Limited information is available for M = Co( ii ) or Co( iii )(NO) − , owing to its chemical non-innocence (volatility) involving NO transfer, sometimes accompanied by Co exchange with other metals or uptake of solvent donors, resulting in intricate and unpredictable formulations. 3…”
mentioning
confidence: 99%